2008
DOI: 10.1038/ni.1625
|View full text |Cite|
|
Sign up to set email alerts
|

Structure of and influence of a tick complement inhibitor on human complement component 5

Abstract: To provide insight into the structural and functional properties of human complement component 5 (C5), we determined its crystal structure at a resolution of 3.1 A. The core of C5 adopted a structure resembling that of C3, with the domain arrangement at the position corresponding to the C3 thioester being very well conserved. However, in contrast to C3, the convertase cleavage site in C5 was ordered and the C345C domain flexibly attached to the core of C5. Binding of the tick C5 inhibitor OmCI to C5 resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
140
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(150 citation statements)
references
References 41 publications
8
140
1
1
Order By: Relevance
“…This highlights the close relationship between inflammation and coagulation and shows a potent and remarkable effect of upstream inhibition of PRRs. OmCI binds directly to C5 and prevents cleavage by the C5 convertases, thus preventing formation of C5a and TCC (28,38). The attenuating effect on TF is in accordance with previous reports describing C5a-dependent TF expression in both neutrophils and endothelial cells (15,16).…”
Section: Discussionsupporting
confidence: 80%
“…This highlights the close relationship between inflammation and coagulation and shows a potent and remarkable effect of upstream inhibition of PRRs. OmCI binds directly to C5 and prevents cleavage by the C5 convertases, thus preventing formation of C5a and TCC (28,38). The attenuating effect on TF is in accordance with previous reports describing C5a-dependent TF expression in both neutrophils and endothelial cells (15,16).…”
Section: Discussionsupporting
confidence: 80%
“…S1B), which at the resolution of 3.6 Å appears to be essentially unchanged relative to the structure of free C5 (21). The interaction of C5 with SSL7 is mediated mainly by the MG1 and MG5 domains with minor contributions from the MG2 and MG6 domains (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…There are now two known binding sites for pathogen proteins inhibiting cleavage of C5. OmCI appears to lock the conformation of C5 and in particular the C345C domain (21), whereas SSL7 binds at the opposite end of the molecule between the distal MG1 and MG5 domains. Both inhibitors appear to block C5 cleavage by interfering with convertase recognition far from C5a.…”
Section: Steric Hindrance and Immune Evasionmentioning
confidence: 99%
“…In C3b, TED and the MG1 domain make contact with each other through an Arg 102 (MG1)-Glu 1032 (TED) salt bridge ( Figure 1B). In contrast, even though inactive C5 showed the same buried TED-MG8 arrangement seen in C3 and C4 [7], the crystal structure of C5b in its complex with C6 showed that its TED and MG1 domains were separated by up to 5 nm and were not in contact ( Figure 1C) [8]. Protein crystal growth requires non-physiological conditions such as low or high salt concentrations, and these may induce non-native protein conformations within the crystal lattice.…”
Section: Introductionmentioning
confidence: 98%